Peran Orang Tua dalam Pengendalian Penggunaan Gawai pada Anak Sekolah Dasar - Fatmah, Nirra (MODELING: Jurnal Program Studi PGMI, 2023)
This paper discusses the role of parents in controlling the use of devices in elementary school children. This paper aims to find out more about how to use devices in elementary school children and how the role of parents in controlling devices in elementary school children. The author uses qualitative research methods where this method aims to provide a complete and in-depth picture of social reality and various phenomena that occur in the community that is the subject of research so as to form the characteristics, character traits and models of these phenomena. Data Collection Techniques Using: observation, documentation. Then data analysis of descriptive analysis methods was carried out to draw conclusions from the role of parents in controlling the use of devices in elementary school children. The results of the study found that the phenomenon of children addicted to devices has been increasingly visible in the last five years. Therefore, therefore how important is the role of parents in controlling, guiding and limiting the use of elementary school children's devices. In addition, parents can also provide strict supervision, provide time limits, provide education about digital, be open in communicating with children and provide good examples. With good roles and responsibilities from parents, the use of devices in elementary school children can be a useful tool for education and entertainment, while still prioritizing children's welfare and development in an increasingly complex digital world.